A proposal for teaching with authentic texts in order to develop social awareness in a language subject in tertiary education - Martínez Lirola, María (Argentinian Journal of Applied Linguistics - ISSN 2314-3576, 2022)
The University of the 21st century has to establish links with society and prepare students for the demands of the working world. Therefore, this article is a contribution to the integral preparation of university students by proposing the use of authentic texts with social content in English lessons so that students acquire emotional and social competencies while still learning content. This article will explain how the choice of texts on global issues such as racism and gender helps students to develop skills such as social awareness and critical thinking to deepen their understanding of discrimination, injustice or gender differences in both oral and written activities. A proposal will be presented which involves using the inauguration speech from Mandela’s presidency and texts with photographs of women so that students analyse them whilst utilising linguistic tools that allow them to explore a text’s social dimension.